Lukasa! (The Devil's Toy). African Inspirations and Western Objects - Walker, Drew (Afrika Focus, 1996)
This paper shows the encounter between an object found among the Luba of Zaire and the art historical treatment of it by western scholars. In this encounter certain tendencies are pointed out which on one hand point to a greatly unackowledged bias of western scholars in their regarding of foreign objects as art, and on the other hand may work to refigure those ways of seeing to form a richer understanding of memory, beauty and history in western scholarly practice. KEYS WORDS : object, memory, Gift (in its German and English senses à la Marcel Mauss)